How Does Owners' Exposure to Idiosyncratic Risk Influence the Capital Structure of Private Companies? - Elisabeth Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper identifies the entrepreneur's exposure to idiosyncratic risk as an important determinant of the capital structure of private companies. The exposure to idiosyncratic risk is approximated by the share of personal net worth invested in one company (SNWI). Exposure to idiosyncratic risk increases cost of equity capital since higher equity returns are required as compensation. This makes bank financing more attractive. We find that SNWI increases the demand for new bank loans whereas we cannot identify an effect on the supply. Equilibrium values of leverage increase significantly in SNWI but there is no effect on the equilibrium interest rate.
More recent version: http://hdl.handle.net/10419/28611
Keywords: G30; G32; 330; entrepreneurial investment; capital structure; underdiversification; private companies; Kapitalstruktur; Eigenkapital; Kapitalkosten